VALIDATION OF SODIUM NITROPRUSSIDE IN VISIBLE SPECTROPHOTOMETRIC DETERMINATION OF TRIPOLIDINE HYDROCHLORIDE - MN, ACHARYULU; PVSR, MOHANA RAO; KOTI I, SIVA RAMA (Innovare Journal of Sciences, 2020)
Objective: A simple and sensitive extractive visible spectrophotometric method is developed for the assay of triprolidine hydrochloride using sodium nitroprusside. Methods: Based on color development with amino groups, presence, which is basic, may be due to the formation of inner complex replacing H2O by the tertiary amino group present in the drug. Results: The colored products exhibit absorption λmax at 447 nm. Regression analysis of Beer–Lambert plots showed good correlation in the concentration ranges (40–240) μg/ml and correlation coefficients are 0.994. The Sandell’s sensitivities 2.6373×10−2 (1 mole cm−1) and molar absorptivity value are 1.1938×104 (g cm−2). Recovery studies are found to be 99.708–99.786. Conclusion: The method can be applied successfully for the estimation of the drug in the presence of other ingredients that are usually present in formulations.